Classification of Visual Cortex Plasticity Phenotypes following Treatment for Amblyopia. (3rd September 2019) - Balsor, Justin L.; Jones, David G.; Murphy, Kathryn M.
Abstract : Monocular deprivation (MD) during the critical period (CP) has enduring effects on visual acuity and the functioning of the visual cortex (V1). This experience-dependent plasticity has become a model for studying the mechanisms, especially glutamatergic and GABAergic receptors, that regulate amblyopia. Less is known, however, about treatment-induced changes to those receptors and if those changes differentiate treatments that support the recovery of acuity versus persistent acuity deficits. Here, we use an animal model to explore the effects of 3 visual treatments started during the CP (n = 24, 10 male and 14 female): binocular vision (BV) that promotes good acuity versus reverse occlusion (RO) and binocular deprivation (BD) that causes persistent acuity deficits. We measured the recovery of a collection of glutamatergic and GABAergic receptor subunits in the V1 and modeled recovery of kinetics for NMDAR and GABAA R. There was a complex pattern of protein changes that prompted us to develop an unbiased data-driven approach for these high-dimensional data analyses to identify plasticity features and construct plasticity phenotypes. Cluster analysis of the plasticity phenotypes suggests that BV supports adaptive plasticity while RO and BD promote a maladaptive pattern. The RO plasticity phenotype appeared more similar to adults with a high expression of GluA2, and the BD phenotypes were dominated by GABAA α 1, highlighting that multiple plasticity phenotypes can underlie persistent poor acuity. After 2-4 days of BV, the plasticity phenotypes resembled normals, but only one feature, the GluN2A:GluA2 balance, returned to normal levels. Perhaps, balancing Hebbian (GluN2A) and homeostatic (GluA2) mechanisms is necessary for the recovery of vision.